Pengembangan Lembar Kegiatan Peserta Didik Berbasis Science, Environment, Technology and Society (SETS) pada Materi Dinamika Rotasi dan Keseimbangan Benda Tegar Kelas XI MIA - Fauzi, M. Rafif; jannah, raudhatul (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
The purpose of this study is to produce student worksheets based on science, environment, technology and society on the material dynamics of rotation and balance of rigid objects class XI MIA MAN 2 Padang City which are valid, practical and effective to increase students' interest in learning. This type of research is research and development (research and development) using the 4-D model starting from the definition stage (define), the design phase (design), the stage of development (develop), and the stage of dissemination (disseminate). The validity test of LKPD was seen in terms of the feasibility of content, media and language by five experts. Practicality test seen from the ease of using LKPD by two physics educators and 13 students of class XI MIA 2 MAN 2, Padang City. Test the effectiveness of LKPD by looking at the interests of students in class XI MIA MAN 2, Padang City. The instrument used in the test of validity, practicality and effectiveness using a questionnaire with a Likert scale and analyzed with percentage techniques. The results showed that science, environment, technology and society-based LKPD on the material of rotational dynamics and rigid body balance produced valid, practical and effective LKPD with very valid criteria (89.54%), very practical criteria (96.91%) and criteria very effective (76.49%).